Housing Transitions and Recovery of Older Adults Following Hurricane Sandy. (20th October 2018) - Merdjanoff, Alexis A; Piltch-Loeb, Rachael; Friedman, Sarah; Abramson, David M
Abstract: Objectives: This study explores the effects of social and environmental disruption on emergency housing transitions among older adults following Hurricane Sandy. It is based upon the Sandy Child and Family Health (S-CAFH) Study, an observational cohort of 1, 000 randomly sampled New Jersey residents living in the nine counties most affected by Sandy. Methods: This analysis examines the post-Sandy housing transitions and recovery of the young-old (55–64), mid-old (65–74), and old-old (75+) compared with younger adults (19–54). We consider length of displacement, number of places stayed after Sandy, the housing host (i.e., family only, friends only, or multi-host), and self-reported recovery. Results: Among all age groups, the old-old (75+) reported the highest rates of housing damage and were more likely to stay in one place besides their home, as well as stay with family rather than by themselves after the storm. Despite this disruption, the old-old were most likely to have recovered from Hurricane Sandy. Discussion: Findings suggest that the old-old were more resilient to Hurricane Sandy than younger age groups. Understanding the unique post-disaster housing needs of older adults can help identify critical points of intervention for their post-disaster recovery.